Animal Resistance in the Global Capitalist Era - Colling, Sarat (Book collections on Project MUSE., 2021)
"This book examines the context, meaning, and implications of animals' resistance to human exploitation from a perspective that considers both the animals' lived experiences and what their resistance reveals about the societies in which they resist"--